2001
DOI: 10.1021/jp012168s
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Basicities of Phosphorus Imines and Ylides:  A Theoretical Study

Abstract: A density functional theory (B3LYP/6-311+G**), ab initio (HF/3-21G*), and semiempirical (PM3) study of intrinsic basicities, protonation energies, or protonation enthalpies of organic phosphorus imine (iminophosphorane) including phosphazene, phosphorus ylide (phosphorane), and phosphine superbases has been performed. The study shows that representatives of the first two classes of the above-mentioned organic superbases can reach the basicity level of the strongest inorganic superbases such as alkali-metal hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(141 citation statements)
references
References 39 publications
8
131
1
1
Order By: Relevance
“…Therefore, one can safely conclude that aromatization, as well as cationic and anionic resonance in the corresponding conjugate acids and bases, are the key concepts in designing neutral organic superbases and superacids. These ideas, combined with other intrinsically highly basic functional groups such as S=N [42] and iminophosphorane [43] and new general notions such as the use of zwitterionic systems [44] or cooperative multiple intermolecular hydrogen bonding, [45] will undoubtedly close the gap which now separates the ladders of superbases and superacids.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one can safely conclude that aromatization, as well as cationic and anionic resonance in the corresponding conjugate acids and bases, are the key concepts in designing neutral organic superbases and superacids. These ideas, combined with other intrinsically highly basic functional groups such as S=N [42] and iminophosphorane [43] and new general notions such as the use of zwitterionic systems [44] or cooperative multiple intermolecular hydrogen bonding, [45] will undoubtedly close the gap which now separates the ladders of superbases and superacids.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include amides and imidates, [19] cyclic and acyclic guanidines, [20][21][22][23] phosphazenes, [24][25][26] quinoimines and related systems, [27] quinolylboranes, [28] extended 2,5-dihydropyrrolimines [29] and C 2 diamines. [30] The extensive theoretical and experimental work carried out by Koppel, Leito and co-workers should be singled out as it includes both the theoretical design and the synthesis of organic bases and superbases as well as measurements of their pK a values in various solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In general it is found that, with the increasing value of AE R , the bond angles and increase, whilst those for , and decrease; concomitantly, the bond length a decreases, whilst b, c, d and e increase. Although the present structural data refer to molecules in their unperturbed ground state in the crystalline solid and the basicity measurements were made in nitrobenzene solution (Feakins et al, 1965(Feakins et al, , 1968Feakins, Last et al, 1969;, where the molecule is perturbed by the approach of a proton (Koppel et al, 2001), there is a de®nite relationship between the molecular parameters of (2a)±(2g) and the substituent basicity constant, analogous to the effects observed previously (Bes Ëli et al, 2002). Other molecular parameters, such as Á(PÐN) values and the sum of the bond angles AENHsp and AENCsp in the series of molecules (2a)± (2g), also decrease as AE R increases, indicating a similar trend in increasing electron density provided by the X substituents, from X = Cl through to X = NHBu t .…”
Section: Discussionmentioning
confidence: 58%